INDIAN DERIVATIVES MARKET - GLOBAL PERSPECTIVE - VINEET PRABHA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The presence of risk is a defining feature of most financial and commodity markets. The dynamics of demand and supply are the forces that, over the course of time, are responsible for causing price fluctuations in a variety of goods, including agricultural and nonagricultural products. The amount of international trade and business has significantly increased as a result of the globalisation and liberalisation wave that has been sweeping the globe over the course of the last two decades. Due to the quick and unpredictable changes in interest rates, exchange rates, and price of financial assets as a result of this, the business world is now exposed to an uncontrollable amount of financial risk. Given the current climate of extreme uncertainty in the business world, risk management is more crucial than ever. An impressive feat of financial engineering was the creation of the derivatives market. Risk associated with the underlying asset's fluctuating value was mitigated in a way that was both cost-effective and time-efficient. It has been relatively recent for India to experience the emergence and growth of a derivatives market. The derivatives market has grown exponentially in terms of both the number of contracts traded and the volume of contracts since it first opened in June of 2000. From Rs. 2365 crore in the previous fiscal year, 2000- 2001, the market's revenue increased to Rs. 110,104,82.20 crore in 2008-2009. In just eight years, India's derivatives market has grown to become one of the world's largest. This rapid expansion has allowed it to surpass the cash segment in terms of both turnover and the number of contracts traded. This research looks at the development of derivative trading, the nature of derivative products, the history of related policies and regulations, the current state of the derivatives market in India, and its potential in the years to come. Some of the space is also devoted to a discussion of the global derivatives markets and how they stack up against India's derivatives market.